Paliperidone extended-release: does it have a place in antipsychotic therapy? - Carlos Schönfeldt-Lecuona; Markus A Kölle; Maximilian Gahr; et al (Dove Medical Press, 2011)
Maximilian Gahr1,*, Markus A Kölle1,*, Carlos Schönfeldt-Lecuona1, Peter Lepping2, Roland W Freudenmann11Department of Psychiatry and Psychotherapy, University of Ulm, Ulm, Germany; 2Department of Psychiatry, Glyndwr University, Wales, UK *Both authors contributed equally and their order was determined by coin toss.Abstract: Paliperidone (9-hydroxy-risperidone), the active metabolite of risperidone, was approved for treating schizophrenia worldwide in 2006 as paliperidone extended-release (PER), and became the first second-generation antipsychotic specifically licensed for treating schizoaffective disorder in 2009. However, at the same time, its comparatively high cost gave rise to concerns about the cost-effectiveness of PER as compared with its precursor, risperidone. This paper reviews the existing knowledge of the pharmacology, kinetics, efficacy, tolerability, and fields of application of PER, and compares PER with risperidone in order to determine whether it has a place in antipsychotic therapy. An independent assessment of all relevant publications on PER published until July 2010 was undertaken. PER has a unique pharmacological profile, including single dosing, predominantly renal excretion, low drug–drug interaction risk, and differs from risperidone in terms of mode of action and pharmacokinetics. High-level evidence suggests that PER is efficacious and safe in schizophrenia, schizoaffective disorder, and acute manic episodes. There is a striking lack of published head-to-head comparisons between PER and risperidone, irrespective of indication. Low-level evidence shows a lower risk for hyperprolactinemia and higher patient satisfaction with PER than with risperidone. PER adds to the still limited arsenal of second-generation antipsychotics. In the absence of direct comparisons with risperidone, it remains difficult to come to a final verdict on the potential additional therapeutic benefits of PER which would justify its substantially higher costs as compared with risperidone. However, in terms of pharmacology, the available evidence cautiously suggests a place for PER in modern antipsychotic therapy.Keywords: antipsychotic treatment, paliperidone, extended-release, second-generation antipsychotics, psychopharmacology, schizophrenia, bipolar disorder